ANALISIS PROSEDUR PENJAMINAN KREDIT PADA PT JAMINAN KREDIT DAERAH (JAMKRIDA) KALTIM TAHUN 2018 - Makmur Makmur; Aris Tri Cahyono; Novita Novita (Jurnal Eksis, 2019)
The purpose of this research is to find out the credit guarantee procedure used by PT Jamkrida Kaltim. The analytical tools used in this study are business feasibility, complementary credit, substitution of compensation, temporary takeover of the risk of bad credit, involvement of three parties, subrogation receivables, and credit control cooperation. The results of this study indicate that the credit guarantee procedures found at PT Jamkrida Kaltim still have a difference in principle, namely the principle of substituting collateral between work practices at PT Jamkrida Kaltim and the principle according to Yasabari and Dewi in a book entitled Credit Guaranteed to Bring UKMK to Access Financing.